A study on the activity concentration of Po-210 in the marine environment of the Kapar coastal area - Lubna A.; Nik Azlin N. A.; Afiza Suriani S; Mohamed, C.A.R (2011)
The distribution of a natural radionuclide (Po-210) in seawater, total suspended solid (TSS), sediment and marine organisms was quantified using alpha spectrometry at the coastal area of Kapar, Malaysia. It was observed that the Po-210 activity in TSS was much higher than that of water and sediment samples. The ranges of Po-210 activity in organism samples were 4.12±0.11 Bqkg-1 to 7.49±0.14 Bqkg-1 (Arius maculatus), 8.66±0.28 Bqkg-1 to 44.47±0.83 Bqkg-1 (Penaeus merguiensis), 55.59±1.07 Bqkg-1 to 161.68±4.21 Bqkg-1 (Anadara granosa) and 45.70±1.77 Bqkg-1 to 96.44±2.19 Bqkg-1 (Perna viridis). There are significant correlations between the total weight and Po-210 concentration for all the organisms sampled. The concentration factors of Po-210 for the organisms calculated were 1851.42 (Arius maculatus), 14296.58 (Penaeus merguiensis), 95314.84 (Anadara granosa) and 27128.18 (Perna viridis). Therefore, it can be assumed that mollusks can contribute a higher radiation to seafood consumers in the coastal area of Kapar